Examining the Gm18 and mG Modification Positions in tRNA Sequences - Mayavan Subramanian; Thangavelu Srinivasan; Dorairaj Sudarsanam (Genomics & Informatics)
The tRNA structure contains conserved modifications that are responsible for its stability and are involved in the initiation and accuracy of the translation process. tRNA modification enzymes are prevalent in bacteria, archaea, and eukaryotes. tRNA Gm18 methyltransferase (TrmH) and tRNA m1G37 methyltransferase (TrmD) are prevalent and essential enzymes in bacterial populations. TrmH involves itself in methylation process at the 2'-OH group of ribose at the 18th position of guanosine (G) in tRNAs. TrmD methylates the G residue next to the anticodon in selected tRNA subsets. Initially, m1G37 modification was reported to take place on three conserved tRNA subsets (tRNAArg, tRNALeu, tRNAPro); later on, few archaea and eukaryotes organisms revealed that other tRNAs also have the m1G37 modification. The present study reveals Gm18, m1G37 modification, and positions of m1G that take place next to the anticodon in tRNA sequences. We selected extremophile organisms and attempted to retrieve the m1G and Gm18 modification bases in tRNA sequences. Results showed that the Gm18 modification G residue occurs in all tRNA subsets except three tRNAs (tRNAMet, tRNAPro, tRNAVal). Whereas the m1G37 modification base G is formed only on tRNAArg, tRNALeu, tRNAPro, and tRNAHis, the rest of the tRNAs contain adenine (A) next to the anticodon. Thus, we hypothesize that Gm18 modification and m1G modification occur irrespective of a G residue in tRNAs.